Removing Duplicate URLs based on URL Normalization and Query Parameter - Goel, Kavita; Shankar Prasad, Jay; Hilal, Saba (International Journal of Engineering and Technology, 2018)
Searching is the important requirement of the web user and results is based on crawler. Users rely on search engines to get desired information in various forms text, images, sound, Video. Search engine gives information on the basis of indexed database and this database is created by the URLs through crawler. Some URLs directly or indirectly leads to same page. Crawling and indexing similar contents URLs implies wastage of resources. Crawler gives such results because of bad crawling algorithm, poor quality Ranking algorithm or low level user experience. The challenge is to remove duplicate results, near duplicate document detection and elimination to improve the performance of any search engine. This paper proposes a Web Crawler which performs crawling in particular category to remove irrelevant URL and implements URL normalization for removing duplicate URLs within particular category. Results are analyzed on the basis of total URL Fetched, Duplicate URLs, and Query execution time. Â Â